Vulnerable Groups of Population in Romania - Mihăilescu, Adina (Calitatea Vieții, 2015)
The majority of Romanian households have a consumption centered on satisfying the basic needs. The predominantly low level of income of the population has not allowed for savings in the years of economic growth before the crisis, which has caused more degradation in the living conditions during the crisis – degradation far below the decent minimal consumption, in all the categories of households. In this study we analyze changes in the Romanian landscape of household incomes and the impact of wage and child allowance from the living standard of population, in July 2015.